Tsunami Disaster Awareness for Elementary School Communities in the South Beach Area of Kulon Progo District - Wiyatmo, Yusman; Sudomo, Joko (YRU Journal of Science and Technology, 2018)
This research is aimed to: 1) implement the module of tsunami awareness in elementary school communities in Kulonprogo district, 2) produce the tsunami simulation video, 3) produce the video of tsunami mitigation technique, and 4) know the respons of elementary school communites about the training of mitigation and management of tsunami dissater. The methode which is used in this research is 4D model. It is developed the instruments of tsunami simulation video, the video of mitigation and management of tsumami dissaster.The subjects of this research consist of 137 elementary school community. The data of this research consist of elementary school communities respons about the module, validation data of tsunami simulation video, and validation data of the video of mitigation and management of tsunami dissaster.The reliability of instrument is determined using the percentage of agreement (PA) from the validator. The results show: 1) the responds of elementary school communities related with module is 3.44 (very good), the PA of tsunami simulation video is 96.57% (reliable), the quality 3.45 (very good), 3) the VCD of mitigation and management of tsunami disaster has the PA of 96.06% (reliable), quality score of 3.75 (very good), 4) the responds of elementary school communities about the training of tsunami mitigation is 3.52 (very good)